Influence of operating parameters on development of polyethylene oxide-like coatings on the surfaces of polypropylene films by atmospheric pressure cold plasma jet-assisted polymerization to enhance their antifouling properties. (December 2018) - Pandiyaraj, K.N.; Arun Kumar, A.; RamKumar, M.C.; Padmanabhan, P.V.A.; Trimukhe, A.M.; Deshmukh, R.R.; Cools, P.; Morent, R.; De Geyter, N.; Kumar, V.; Gopinath, P.; Jaganathan, S.K.
Abstract: In this study, we investigated the deposition of a polyethylene oxide (PEO)-like coating on the surfaces of polypropylene (PP) films via atmospheric pressure cold plasma jet-assisted polymerization using ethylene glycol dimethyl ether as a precursor. The PEO-like coatings were deposited using different operating parameters (deposition potential and monomer flow rates) and we determined their effects on the film properties, such as the topography, surface chemistry, and surface free energy, based on atomic force microscopy, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and contact angle measurements. The interfacial tension between various biological liquids and the PEO-like film surfaces were studied in detail. The antifouling properties of the PEO-like films were examined in vitro, including protein adsorption and platelet adhesion. The results showed that the retention of the PEO-like character and the formation of new functional groups were highly dependent on the operating parameters. Significant changes in the film topography and wettability were obtained by further regulating the plasma operating parameters. All of the PEO-like films had good antifouling properties according to the in vitro analysis results. Highlights: Polyethylene oxide (PEO)-like coating deposited on polypropylene films. Effects of operating parameters on properties of PEO-like coatings investigated. Interactions between PEO-like coatings and blood components examined in detail.